Covered frozen elephant trunk technique for prevention of distal stent graft-induced new entry. (16th February 2022) - Okamura, Homare; Kitada, Yuichiro; Wada, Yohnosuke; Adachi, Hideo
Abstract: Distal stent graft-induced new entry is not rare after frozen elephant trunk implantation. We report a case of covered frozen elephant trunk placement for prevention of distal stent graft-induced new entry. Coverage of the rigid distal stent edge using a graft reduces mechanical stress on the intima and radial force of the distal stent; therefore, this technique can potentially prevent distal stent graft-induced new entry. Abstract : The frozen elephant trunk (FET) technique is widely used to promote aortic remodelling in cases of acute type A aortic dissection.